2019
DOI: 10.1186/s12903-018-0706-0
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge, attitude and compliance of infection control guidelines among dental faculty members and students in KSU

Abstract: BackgroundInfection is one of the most crucial problems in health care services worldwide. It is considered one of the most important causes of morbidity and mortality associated with clinical, diagnostic and therapeutic procedures. Therefore, the purpose of this study was to investigate knowledge, attitude, and compliance with recommended infection control guidelines among dental faculty members and students at King Saud University, Riyadh, Kingdom of Saudi Arabia.MethodsA cross-sectional study was conducted … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
39
1
3

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(61 citation statements)
references
References 15 publications
7
39
1
3
Order By: Relevance
“…Dentist's compliance with these guidelines and recommendations have been recently studied in different parts of the world. [13,14] These studies indicate that there are gaps in some dentist's knowledge regarding modes of transmission of infectious diseases so the objective of this study was to evaluate the knowledge, attitude, and practice regarding infection control procedures among dentists of Karachi, Pakistan, therefore, we could then identify the areas where improvements can be made in a dental setting.…”
Section: Introductionmentioning
confidence: 99%
“…Dentist's compliance with these guidelines and recommendations have been recently studied in different parts of the world. [13,14] These studies indicate that there are gaps in some dentist's knowledge regarding modes of transmission of infectious diseases so the objective of this study was to evaluate the knowledge, attitude, and practice regarding infection control procedures among dentists of Karachi, Pakistan, therefore, we could then identify the areas where improvements can be made in a dental setting.…”
Section: Introductionmentioning
confidence: 99%
“…• Manual instruments are recommended to minimize the aerosol generation. and practice levels regarding the same are low [31][32][33][34][35][36]. Findings indicate that lack of compliance with ICP is multifactorial, and compliance with recommended IC guidelines is challenging, and the results of some studies indicate that compliance is achievable, even in medium and large group practices [32,[37][38][39].…”
Section: Manual Instrumentsmentioning
confidence: 99%
“…In Saudi Arabia, the previous published researches on infection control compliance of dental students in College of Dentistry, Jazan [13], King Khalid University, Abha [9], and King Saud University, Riyadh [14], [15] reported that their compliance was satisfactory but more efforts are recommended to improve it. However, all these researches were based on subjective self-reported data through answering questionnaire which according to Ayub et al [16] assumptions could not accurately reflect the actual compliance and might resulted in overestimation of compliance.…”
Section: Dentalmentioning
confidence: 99%
“…th grade students in dress code and cubic violations and lower in attitude violations outside the cubicle in both grades. These findings could be accounted for the fact that senior students who had clinical experience become more aware of cross infection risk inside the clinics while having much heavier load to finish their clinical requirements to be eligible for graduation might lead them to miss some infection control regulations outside the treatment cubicle [15].…”
Section: Student Clinics At Umm Al-qura Dental Teachingmentioning
confidence: 99%